Family 13 in St. John's Gospel, A Computer Assisted Phylogenetic Analysis. - Jac Perrin (New Testament Tools, Studies and Documents, 2018)
In Family 13 in Saint John's Gospel , Jac Perrin innovatively applies phylogenetic software to shed new light on Family 13 membership. To date, the relocation of the Pericope Adulterae from its traditional location in John 7:53 has been the sole criterion of Family 13 filiality. This book demonstrates the inadequacy of this criterion, and proposes new criteria in its stead. Nineteen potential Family 13 witnesses are analyzed by means of a sampling process developed by David Parker, identifying eight witnesses inappropriately nominated as Family 13 members. This analysis is corroborated by a complete computer assisted collation of all variant readings in all known Family 13 witnesses. Lastly, the volume offers a comprehensive stemma representing the entire Johannine corpus of ten confirmed Family witnesses in constellation.